A comprehensive review on thermal conductivity and viscosity of nanofluids - Urmi, Wajiha Tasnim; Rahman, Md Mustafizur; Kadirgama, Kumaran; Zetty Akhtar, Abd Malek; Wahaizad, Safiei (Penerbit Akademia Baru, 2022)
The innovation of nanofluids, a novel working fluid, has presented the development of heat transfer properties in machining, automotive engine cooling systems, pumping power and others to optimize the overall system. Nanofluids have pulled in scientists' cogitation from various fields in designing new thermal systems for different engineering applications due to their distinctive thermophysical properties and prospective applications. Long term stability, improved thermal conductivity, and viscosity are the principal fundamental expectations in nanofluids research to achieve better heat transfer performance. In the previous couple of decades, various investigations have been completed to explore the nanofluids properties augmentation. For instance, kerosene-based oleic acid-coated Fe3O4 nanofluids showed 300% improvement of thermal conductivity, and water-based single-walled carbon nanotube revealed 320% improvement of viscosity. This paper presents a survey of recent exploration outcomes focusing on the thermal conductivity, viscosity, flow characteristics of hybrid nanofluids, including the preparation method of nanofluids utilized in different applications. Additionally, the elements that impact nanofluids' thermophysical properties, challenges of nanofluids, and fundamental outline and analysis of most recent research studies have been discussed and referenced. Finally, although the applications of nanofluid are increasing in several engineering sectors due to advanced discoveries of nanofluid, yet, requires more research focusing on the study of various sorts of nanofluids, different combinations of several types of nanoparticles, blending proportion and identifying the component which adds to the up-gradation of heat transfer to commercialize the nanofluids in practical fields.